THU0531 The Initial Treatment of Systemic Juvenile Idiopathic Arthritis: An International Collaboration Among 7 Registries. (9th June 2015) - Beukelman, T.; Berntson, L.; Duffy, C.M.; Guzman, J.; Kimura, Y.; Klotsche, J.; Magnusson, B.; Minden, K.; Nordal, E.; Santos, M.J.; Thomson, W.; Zilhao, C.; et al.
Abstract : Background: Systemic JIA (sJIA) treatment has changed dramatically with the introduction of biologic agents, although treatment approaches likely differ by region. Objectives: We compared the initial treatment of sJIA at pediatric rheumatology centers (PR) in the United States (US), United Kingdom (UK), Germany (GER), Portugal (POR), Canada (CAN), Sweden (SWE), and the Nordic countries (NORD) using prospectively collected registry data. Methods: Data were extracted locally by the following JIA Registries: Childhood Arthritis and Rheumatology Research Alliance Registry (US); Childhood Arthritis Prospective Study (UK); National Pediatric Rheumatology Database (GER); Reuma.pt (POR); Research in Arthritis in Canadian Children Emphasizing Outcomes (CAN); the Swedish National JIA Registry (SWE) and the Nordic JIA Cohort (NORD; no duplicate patients with SWE). Prospectively collected treatment data covering the first year of disease (defined as 9 to 15 months following first encounter with PR) for children diagnosed with SJIA since 2009 were included. We also collected data on the presenting characteristics (defined as within 2 months of the first encounter with PR) of all children with sJIA within each registry. Data were compared across registries using ANOVA and chi-square. Results: Overall, there were data available about the presenting characteristics for 486 patients and about the first year of treatment for 431 patients. There were differences in the sex distribution of the patients (more females in US) and in the elapsed time from symptom onset to evaluation by PR (shorter duration in GER). There were differences in presenting characteristics, including less frequent evanescent rash in GER and POR, less frequent lymphadenopathy in GER and CAN, and more frequent hepatosplenomegaly in GER. The proportion of patients receiving each medication in the first year of disease is shown in the Table . The use of all medication classes was significantly different among the registries (p<0.002 in all cases). Systemic glucocorticoids were less frequently used in UK. Methotrexate was more frequently used in UK and NORD. Biologics were more frequently used in US and NORD and less frequently used in GER. Conclusions: Presenting characteristics of children with sJIA were different among the registries. It is unknown how much of this variation may be attributable to differences in ascertainment and patient enrollment. There were marked differences in the treatment of sJIA in the first year of disease among the registries, particularly with respect to the use of biologic agents. The impact of these different treatment approaches on patient outcomes is not known, but is worthy of further investigation. Disclosure of Interest: T. Beukelman Consultant for: Novartis; Genentech/Roche; UCB, L. Berntson: None declared, C. Duffy: None declared, J. Guzman: None declared, Y. Kimura: None declared, J. Klotsche: None declared, B. Magnusson: None declared, K. Minden Grant/research support from: Abbvie, Pfizer, Consultant for: Abbvie, Pfizer, Roche/Chugai, Pharm-Allergan, E. Nordal: None declared, M. Santos: None declared, W. Thomson: None declared, C. Zilhao: None declared, K. Hyrich Consultant for: Abbvie, Pfizer